Assessment of Membrane Bioreactor in Treating Spent Sulfidic Caustic Wastewater: Effects of Organic Biomass Concentration and Solid Retention Time (Chemical Engineering Research Bulletin, 2017)
This paper presents a study on the performance of an Aerobic Submerged u-shaped membrane bioreactor (ASMBR) in treating sulfidic spent caustic (SSC) in terms of mixed liquor suspended solid (MLSS) concentration and solid retention time (SRT). SSC wastewater is categorized as high strength wastewater and consists of high inorganic and organic matter. U-shape membrane bioreactors have a higher tendency to foul compared to other types of MBR. MLSS concentration and SRT are the major parameters when operating membrane bioreactor. In this study, COD removal recorded reduction of more than 95% for average MLSS concentration runs and 90% for SRTs runs. Meanwhile, sulfide was removed 99%, and formed up to 79% of sulfate. The biofouling for MLSS concentration and SRTs were observed through TMP rate change and TMP average performance, TMP trend and SMP and EPS trends. Biocake layer and biolayer deposited on membrane surface was found influenced by biomass, the inert particulate biomass products accumulating in the reactor.Chemical Engineering Research Bulletin 19(2017) 102-110